DAMPAK JANGKA PANJANG DIGITALISASI LAPORAN KEUANGAN DAN IMPLIKASINYA TERHADAP KINERJA KEUANGAN UMKM DI RIAU - Serly Novianti; Zaharman Zaharman; Arini Arini (Komunitas Manajemen Kompetitif, 2026)
The advancement of digital technology promotes micro, small, and medium enterprises (MSMEs) to revolutionize their business finances. The digitization of financial statements constitutes one of the critical endeavors to enhance the efficacy of transaction documentation, the caliber of financial information, and organizational decision-making. This investigation seeks to examine the enduring impact of financial statement digitization on the financial performance of MSMEs in Riau Province. This analysis employs a quantitative methodology utilizing a survey technique involving 400 MSMEs in Riau Province. Data was amassed through questionnaires and scrutinized employing simple linear regression with the assistance of SPSS software. The research variables encompass the digitization of financial statements as an independent variable and the financial performance of MSMEs as a dependent variable. The outcomes of the inquiry indicate that the digitization of financial statements exerts a positive and significant influence on the financial performance of MSMEs. The value of the determination coefficient reveals that the digitization of financial statements is capable of elucidating the majority of the variations in the financial performance of MSMEs. These revelations suggest that the implementation of digital financial statements can enhance the efficiency of financial management, cash flow stability, and the quality of organizational decision-making in the long term. This research conveys an implication that digital transformation in MSME financial reporting necessitates ongoing encouragement through the enhancement of the capacity of business actors and the broader utilization of financial technology